Corporate tax competition between firms - Simon Loretz; Padraig J. Moore (University of Salzburg, Department of Social Sciences and Economics, 2009)
Firms' tax planning decisions, similar to their other operational decisions, are made in a competitive environment. Various stakeholders observe the tax payments and evaluate these against the relevant peer group, which creates interdependencies in the tax planning activities of firms. Introducing the concept of reputational loss we show the positive interdependence in a theoretical model and test it in a spatial econometric model. Empirical evidence suggests that benchmarking takes place both within countries and within industries, however for the latter it is important to include firms in large non-EU OECD countries. Further, the analysis shows that spatial interdependence is stronger for the largest firms and if they have an average effective tax rate above the statutory tax rate.
Keywords: H25; M40; 330; Corporate Taxation; Benchmarking; Tax Competition; Spatial Econometrics